ASSESSMENT OF FIRST AID KNOWLEDGE AMONG PHYSICAL EDUCATION STUDENTS - Rida Qasim; Aqib Liaqtat; Sehab Afzal; M. Sajjad Ali Gill; Rashna Sehar; Ali Islam (International Journal of Contemporary Issues in Social Sciences, 2024)
Accidents and injuries are part of daily events, and many of these injuries are initially treated by untrained personnel due to lack of health care providers on the accident site. These accidents and injuries can cause serious consequences if not dealt with properly. Therefore it is necessary to assess the first aid knowledge among students of physical education in the sports sciences department. As first aid knowledge is very important in everyday situation in sports and other daily activities. Therefore, implementing correct first aid measures is vital for victims in emergency cases and helps to improve the overall outcome of the first aid process in emergency situations. The purposes of the study was to assess the first aid knowledge among the students of department of sports sciences and physical education in university of the Punjab, Lahore. It was cross sectional survey study which was conducted in the department of sports science and physical education in university of the Punjab, Lahore. The participants both male and female (N=50) having age 18-25 years of the study were taken from sports sciences department by using simple random sampling technique. The data was collect by using FAA questionnaire developed by Ransone& Dunn Benett (1999. The researcher visited the sport sciences department of Punjab University to collect data from respondents. The researcher took data and filled all questionnaire from respondents in supervision. After collecting data, the data was analyzed through SPSS version -27 (Statistics Power Service Solution) by using Chi Square test of association and results of students knowledge was presented in the form of Pie Chart. It was concluded that there was a high significant association between Physical education student’s knowledge and their gender.